Politicization of Religion: Religion in Political Discourse - Syarif, Fajar (LP2M - Universitas Islam Negeri (UIN) Walisongo, 2017)
This article discusses the position of religion in politic that has relation to leadership. The main argumentation of this research is religion will constantly become a political power and social movement. In one side the research has different opinion from the integration politic paradigm and secular that proposed by Hasan al-Bannā and ‘Alī Abd. al-Rāziq, but in another side, it has reinforced the two paradigms. By using literature study and descriptive method and philosophical historical approach, it indicates Islam will constantly exist and has influence in the political process. Although Islam is not depending on politic and on the contrary. Islam and politic are both integrated dimension of life, so both are not able to be separated from social politic dynamics.Artikel ini membahas kedudukan agama dalam politik yang berkaitan dengan kepemimpinan. Argumentasi utama penelitian ini adalah bahwa agama tetap akan menjadi kekuatan politik dan gerakan sosial. Di satu sisi penelitian ini berbeda pendapat dengan paradigma politik integrasi dan sekuler yang dikemukakan oleh Hasan al-Banna dan ‘Alî Abd. al-Rāziq, namun di sisi lain memperkuat kedua paradigma tersebut. Dengan menempuh studi kepustakaan dan menggunakan metode deskriptif serta pendekatan filosofis dan historis, penelitian ini menunjukkan bahwa Islam akan tetap eksis dan berpengaruh dalam proses politik. Hakikat Islam meskipun tidak bergantung pada politik dan begitu pula politik tidak bergantung pada Islam. Islam dan politik merupakan dua dimensi yang integral dalam kehidupan, maka keduanya tidak dapat dipisahkan dari dinamika sosial politik.